Iris Melanoma: Management and Prognosis - Andrea Russo; Teresio Avitabile; Michele Reibaldi; Vincenza Bonfiglio; Francesco Pignatelli; Matteo Fallico; Rosario Caltabiano; Giuseppe Broggi; Daniela Russo; Silvia Varricchio; Corrado Spatola; Antonio Basile; et al. (Applied Sciences, 2020)
Iris melanomas represent 2–5% of uveal melanomas. Iris melanomas vary in their size, shape, degree of pigmentation and clinical behavior. The main local clinical complications of iris melanomas are tumor vascularization, ectropion uvea, pupillary distortion, pigment dispersion, sector cataract, chronic uveitis, hyphema and glaucoma with irreversible optic nerve damage. The most effective treatment for iris nevus and melanoma remains debatable; treatment modalities have been proposed depending on the local status as well as the age and general condition of the patient. A melanocytic iris nevus is usually observed until documented progression is identified. In this case, radiotherapy or surgical resection is generally performed. Cataract, glaucoma and limbal stem cell deficiency are usually secondary to radiotherapy, while incomplete tumor excisions, which could lead to recurrence, hemorrhage, vitreous loss, dislocated lens, iridocyclitis, macular edema, retinal detachment, glaucoma and cataract, are related to surgical resection. In some cases, a combination of radiotherapy and surgery is used. Conservative treatment is an efficient alternative to enucleation and allows good local tumor control.